Conservation of Wetlands in India: Critical Review of the Adequacy of Law Suresh Chandra Gairola - Gairola, Suresh Chandra (Indian Forester, 2014)
This paper discusses the status, various laws, regulations and policies, and legal perspective of wetlands conservation in India. The adequacy of existing wetlands conservation laws in India is analysed and suggestions for improvement in conservation initiatives are made. India has a robust framework of laws and policies governing wetlands conservation. High quality research has been done at various governmental and non-governmental institutions. However, considering the magnitude of the efforts needed to conserve wetlands due to ever increasing pressures and treats, the paper argues that existing legal and institutional framework is not adequate to conserve the vital wetlands resources in the country. A large extent of wetlands has been excluded from the existing regulation net exposing them to overexploitation and consequential degradation. Community participation in conservation initiatives at local and regional level need to be strengthened by developing a long term stake. Issues of fair and equitable sharing of resources through sustainable utilization hold the key for wetlands conservation in India.